2011
DOI: 10.5551/jat.9175
|View full text |Cite
|
Sign up to set email alerts
|

Serum Paraoxonase 1 Activity Predicts Arterial Stiffness in Renal Transplant Recipients

Abstract: Aim: Paraoxanase 1 (PON 1) has been shown to protect against atherosclerosis by modifying lipoproteins. Its activity decreases in dialysis patients but is restored after transplantation. Whether it affects arterial stiffness is unclear. In this study we aimed to investigate the effects of PON 1 on arterial stiffness in renal transplant patients. Methods: Seventy renal transplant recipients were enrolled. Arterial stiffness was measured using a Syphmocor device. PON-1 activity was assessed from the rate of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Considering the potential role of PON1 in lipid transfer from LDL-C to HDL-C, it is likely that decreased serum PON1 activity is associated with the increased LDL-C in the olanzapine group. Interestingly, serum PON-1 activity is reported to be negatively correlated with serum LDL-C level 51,52. Furthermore, our finding of a positive correlation between serum PON1 activity and HDL-C level in the olanzapine group is of great interest.…”
Section: Discussionmentioning
confidence: 59%
“…Considering the potential role of PON1 in lipid transfer from LDL-C to HDL-C, it is likely that decreased serum PON1 activity is associated with the increased LDL-C in the olanzapine group. Interestingly, serum PON-1 activity is reported to be negatively correlated with serum LDL-C level 51,52. Furthermore, our finding of a positive correlation between serum PON1 activity and HDL-C level in the olanzapine group is of great interest.…”
Section: Discussionmentioning
confidence: 59%
“…measurement of ABCA1-mediated CEC is a direct index of HDL functionality strictly dependent on serum pre ␤ HDL content, as widely demonstrated ( 8,34,35,41 ), so it renders redundant HDL composition analyses such as HDL pre ␤ content measurement in the present study. The relationship between HDL composition/function and arterial stiffness seems to be underlined also by the recent observation that reduction of paraoxonase-1, an atheroprotective HDL antioxidant component, predicts PWV in renal transplant recipients ( 42 ). The demonstration that PWV in adulthood is infl uenced by atherogenic lifestyle factors in childhood ( 43,44 ) confi rms the existence of a large number of determinants, other than blood pressure and age, able to modify arterial wall over time in asymptomatic subjects.…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies of renal transplant populations revealed that recipient and donor age, hypertension, duration of dialysis, diabetes, and acute rejection were related to increased arterial stiffness [7,13]. In addition, lower serum magnesium [14] and paraoxonase 1 activity [15] have been reported to be independently associated with arterial stiffness. Our results show a similar association between low pre-transplant serum adiponectin level and arterial stiffness, and that those levels are associated with development of NODAT.…”
Section: Discussionmentioning
confidence: 99%